Answer:
Step-by-step explanation:
First, we isolate the variable on the second equation so that we can have an x solution to plug in:
Now, we plug this in to the first equation:
[tex]7(-y+4)^{2} +(-y+4)^{2} =64[/tex]
We can now put the 7 into the parentheses and then square root the equation:
[tex]\sqrt{(-7y+28)^{2}} +\sqrt{(-y+4)^{2}} =\sqrt{64}\\-7y+28-y+4=8\\-8y=40\\y=-40[/tex]
We then plug this in to the original equation to find x
[tex]x+-40=4\\x=-36[/tex]
This means y=-40 and x=-36. I believe that's what you were asking. Let me know if it is something else